Evaluating an interactive teaching approach with personal genotyping to provide pharmacy students with a knowledge base for clinical pharmacogenetics. Issue 3 (9th November 2020) - Arwood, Meghan J.; McDonough, Caitrin W.; Cavallari, Larisa H.; Elsey, Amanda R.; Frye, Reginald F.; Gong, Yan; Langaee, Taimour; Johnson, Julie A.; Wiisanen, Kristin
Abstract: Introduction: Although the majority of pharmacy schools are teaching pharmacogenetics in their curricula, there is limited coverage of important clinical concepts and pharmacists report low comfortability in utilizing pharmacogenetic results. Objectives: To compare the effectiveness of a combined didactic and patient case‐based, interactive teaching approach (including optional personal genotyping) with a traditional didactic teaching strategy on students' knowledge and confidence in their ability to use pharmacogenetic data in clinical decision‐making. Methods: The University of Florida College of Pharmacy offered elective and required courses in personalized medicine from 2014 to 2016. The elective course, Clinical Applications of Personalized Medicine, emphasized interactive patient case‐based teaching and incorporated personal genotype results into learning activities, while the required course, Personalized Medicine, primarily used a didactic lecture‐based format. Students enrolled in both courses concurrently (intervention group) and the required course alone (control group) completed pre‐ and post‐course surveys with patient case‐based assessments to evaluate their knowledge and confidence in their ability to apply genotype data to drug therapy recommendations. Results: Fifty‐two students (intervention: n = 21; control: n = 31) completed both surveys. Between the intervention and control groups respectively, there were no differences in mean pre‐course knowledge (43.1% vs 37.7% questions correct, P = .15) or median confidence scores (35 vs 40, P = .84). Mean post‐course knowledge (65.4% vs 46.9% questions correct, P < .001) and median confidence scores (97 vs 81, P = .0003) were significantly higher in the intervention vs control group, respectively. There was no correlation between students' knowledge and confidence for pre‐course assessment in either group. For the post‐course assessment, knowledge and confidence were positively correlated in the intervention group (adjusted r = .46, adjusted P = .04), but were not correlated in controls. Conclusion: Our data suggest that a combined teaching strategy that employs didactic lecture plus patient‐centered, case‐based teaching and personal genotype application improves students' ability to accurately self‐assess their knowledge in pharmacogenetics.